Pengaruh partisipasi upacara bendera terhadap pembentukan karakter disiplin peserta didik di sekolah dasar - Az-Zahra, Armin Maharita; Adi, Fadhil Purnama (Didaktika Dwija Indria, 2026)
Abstract. Character education, particularly discipline, is crucial for shaping students' personalities from an early age. Despite its importance, disciplinary issues such as tardiness, unexplained absences, and non-participation in ceremonies are still prevalent in elementary schools, negatively impacting character development and academic achievement. Flag ceremonies, routinely held in Indonesian schools like SD Negeri Dalangan 01, are considered an important medium for instilling national values and discipline. However, observations at SD Negeri Dalangan 01 revealed varying levels of participation and discipline among students. This study aimed to deeply examine the positive influence of student participation in flag ceremonies on the formation of their disciplinary character at SD Negeri Dalangan 01. A quantitative method with an associative design was employed, involving 35 students from grades IV, V, and VI selected via Simple Random Sampling. Data were collected using Likert-scale questionnaires for participation and discipline, which demonstrated high validity and reliability. Prerequisite tests confirmed normal distribution, linearity, and no heteroscedasticity. Simple linear regression analysis yielded a regression equation of Yi = 44.378 + 0.446Xi, indicating a positive relationship. The T-test (t-statistic = 4.448 > t-table = 2.035, Sig. = 0.000 < 0.05) confirmed a significant positive influence. The coefficient of determination (R-squared = 0.375) revealed that flag ceremony participation accounts for 37.5% of the variation in disciplinary character formation, with the remaining 62.5% influenced by other unexamined factors. The study concludes that student participation in flag ceremonies significantly influences disciplinary character, highlighting the crucial role of routine ceremonies through positive habituation in instilling disciplinary values.